Matrix metalloproteinases and subclinical atherosclerosis in chronic kidney disease: A systematic review - Kousios, Andreas; Kouis, Panayiotis; Panayiotou, Andrie (My University, 2016)
Background. Cardiovascular disease (CVD) remains a significant problem in Chronic Kidney Disease (CKD). Subclinical atherosclerosis identified by noninvasive methods could improve CVD risk prediction in CKD but these methods are often unavailable. We therefore systematically reviewed whether circulating levels of Matrix Metalloproteinases (MMPs) and tissue inhibitors (TIMPs) are associated with subclinical atherosclerosis in CKD, as this would support their use as biomarkers or pharmacologic targets. Methods. All major electronic databases were systematically searched from inception until May 2015 using appropriate terms. Studies involving CKD patients with data on circulating MMPs levels and atherosclerosis were considered and subjected to quality assessment. Results. Overall, 16 studies were identified for qualitative synthesis and 9 studies were included in quantitative synthesis. MMP-2 and TIMP-1 were most frequently studied while most studies assessed carotid Intima-Media Thickness (cIMT) as a measure of subclinical atherosclerosis. Only MMP-2 demonstrated a consistent positive association with cIMT. Considerable variability in cIMT measurement methodology and poor plaque assessment was found. Conclusions. Although MMPs demonstrate great potential as biomarkers of subclinical atherosclerosis, they are understudied in CKD and not enough data existed for meta-analysis. Larger studies involving several MMPs, with more homogenized approaches in determining the atherosclerotic burden in CKD, are needed.
Keywords: Cardiovascular disease; Chronic Kidney Disease; Matrix Metalloproteinases; Tissue inhibitors